Cost analysis of the prescribing patterns on the management of gouty arthritis in a level 2 hospital from 2009 to 2013 - Triumfante, Shasta Daisy V.
Gout is the most prevalent form of arthritis affecting Filipinos. However, despite the existence of the Philippine Clinical Practice Guidelines (PCPG) for the Management of Gout, existing literature states that poor adherence to the existing quality indicators for the treatment of gout has been observed among physicians. Compliance to the existing clinical practice guidelines may help address this issue but there is a lack of studies on the economic impact of these guidelines on the management of gout. A review of medical records from 2009-2013 was performed in a Level 2 Government hospital to determine the compliance of physicians to the existing PCPG for gout. Results showed low rates of compliance among prescriber for both acute (23.1%) and chronic gout (14.3%). The prescription of a drug not recommended in the PCPG was the most common type of non-compliance for acute gout (83.3%) while the prescription of an inappropriate drug was the most common type of chronic gout (40.0%). The economic implication of the prevailing drug prescribing patterns was assessed by determining the cumulative differences between the standard PCPG drug costs and the actual drug costs. An increase in total drug costs was noted. The low rates of prescriber compliance may reflect poor utilization of the clinical practical guidelines. A higher compliance to the PCPG could have minimized unnecessary additional costs. A review and update of the PCPG could be beneficial because the current version does not include newer anti-gout drugs an some of the recommendations are not specific.